Scalanie i podział nieruchomości nierolnych i nieleśnych a miejscowy plan zagospodarowania przestrzennego - Klat-Wertelecka, Lidia; Klat-Górska, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Consolidation and division proceedings are a procedure which should be applied in view of the principles of spatial order and sustainable development and at the same time it should serve the purpose of rational land development. There is a visible relationship between the process of consolidation and division of land and a local development plan. The analysis of statutory regulations allows drawing a conclusion that the commune in the procedure of changing the local development plan is obliged to comply with the applicable provisions of the resolution on consolidation and division of land. Therefore, it is important to answer the question of whether the detailed terms and conditions of consolidation and division of land should constitute an element which is to be obligatorily specified in the local development plan. Connecting the issue of consolidation and division of land with the assumptions of the local development plan means that if the land development plan is found to be invalid in part or in full it affects the adoption of the resolution on consolidation and division of land.
Keywords: scalenie i podział; miejscowy plan zagospodarowania przestrzennego; zagospodarowanie terenu; uchwała rady gminy; nieruchomość